CRAN-14. ASTROBLASTOMA – A REPORT FROM 3 CASES - Drogosiewicz, Monika (Neuro Oncol, 2018)
Astroblastoma is a rare CNS tumor of glial origin distinguished from other gliomas in the recent International Classification of Tumors of the Central Nervous System proposed by the World Health Organization. We present our experience with 3 astroblastoma patients. Between 2003–2017 among 978 patients with tumors of glial origin treated at our Institution 3 patients (0,3 %) were diagnosed with astroblastoma. There were 2 girls and 1 boy aged 2.5, 3, 5.5 years. Two patients had supratentorial tumors, one tumor was located infratentorially. All patients underwent subtotal tumor resection received pre-irradiation chemotherapy, local irradiation (54Gy) and maintenance chemotherapy. All patients are alive 1, 5 yrs 8 m, 13 yrs2m from diagnosis. Our results as of other authors confirm favorable prognosis and rarity of astroblastoma in pediatric population.